2007
DOI: 10.1021/op700049p
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of Nitrobenzene to 4-Aminophenol over Supported Platinum Catalysts

Abstract: The conversion of nitrobenzene (NB) to p-aminophenol (PAP) takes place by way of an initial partial hydrogenation to produce phenylhydroxyl amine (PHA) which then undergoes an in situ acid-catalyzed rearrangement to PAP. This reaction is most commonly run using Pt/C catalysts in the presence of aqueous sulfuric acid and a surfactant to assist in dispersing the NB throughout the reaction medium. The yield of PAP is closely related to those reaction parameters which facilitate first the partial hydrogenation ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 12 publications
(12 reference statements)
1
18
0
Order By: Relevance
“…It is noteworthy that the best performing one, in terms of both catalytic activity and yield to 4-aminophenol, is Pt/C. This gives the best results also with the biphasic sulfuric acid nitrobenzene system [1][2][3][4][5][6]. Both Pd/C and Rh/C show high hydrogenation activity, but 4-aminophenol yields (in both cases) is lower than that observed in the presence of Pt/C.…”
Section: Influence Of the Catalyst Type On Reaction Rate And Selectivitymentioning
confidence: 98%
See 3 more Smart Citations
“…It is noteworthy that the best performing one, in terms of both catalytic activity and yield to 4-aminophenol, is Pt/C. This gives the best results also with the biphasic sulfuric acid nitrobenzene system [1][2][3][4][5][6]. Both Pd/C and Rh/C show high hydrogenation activity, but 4-aminophenol yields (in both cases) is lower than that observed in the presence of Pt/C.…”
Section: Influence Of the Catalyst Type On Reaction Rate And Selectivitymentioning
confidence: 98%
“…4-Aminophenol is an important raw material for several products in the field of dyes, polymer and pharmaceutics [1][2][3]. For instance, paracetamol (N-acetyl-4-aminophenol) is a widely employed analgesic and antipyretic whose production is in continuous growth, particularly in the Far East region [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Henke and Vaughen [11] showed that NB pathway is feasible using Pt/C catalyst in inorganic acid solution. [12] Meanwhile, corresponding kinetics was also carefully investigated, showing that hydrogenation rate is competitive against rearrangement rate, which limits the PAP selectivity even in concentrated acids. [12] Meanwhile, corresponding kinetics was also carefully investigated, showing that hydrogenation rate is competitive against rearrangement rate, which limits the PAP selectivity even in concentrated acids.…”
Section: Introductionmentioning
confidence: 99%